PENGARUH RIGHT ISSUE TERHADAP KINERJA PERUSAHAAN YANG TERCATAT DI BURSA EFEK INDONESIA - afrira syuhana; syahyunan syahyunan (Universitas Sumatera Utara, 2013)
ABSTRACT This research aimed to determine whether there is difference in companies’s performance before and after the execution of a rights issue, whether there are differences in companies’s performance which execution of a right issue and the companies that do not, and to analyze whether there is a significant influence on companies listed on the Indonesia Stock Exchange. The sample is 26 issuer companies and 26 nonissuer companies as a sample comparison in this research. This research uses secondary data sourced from financial statements of companies listed on the Indonesia Stock Exchange (BEI) and conduct a rights issue from 2007 to 2009. The techniques of hypothesis tests that the first hypothesis is paired sample t test, the second hypothesis is independent sample t test, and the third hypothesis is simple regression analysis. The results of this research in that: 1)There is a difference in a company's financial performance proxied by net profit margin before and after execution of the rights issue. While there is no difference in the company's financial performance proxied by the current ratio, debt ratio, total asset turnover, and return on assets before and after execution of the rights issue, 2) There is no difference in financial performance between companies that conduct a rights issue and the companies that do not, and 3) Right issue influences negatively and significant to the company's financial performance by the debt ratio and the net profit margin. But the right issue influences positively and not significant to the financial performance by the current ratio, and return on assets, and right issue influences negatively and not significant to the company's financial performance by total asset turnover Keywords: Right Issue, Current Ratio, Debt Ratio, Total Asset Turnover, Return on Assets, and Net Profit Margin